"Through the looking glass: envisioning new library technologies" Adopting augmented reality: trends and updates. Issue 9 (6th November 2017) - Fernandez, Peter
Abstract : Purpose: This column aims to summarize developments in augmented reality and use those developments to help explain trends that influence the likelihood of mainstream adoption. Design/methodology/approach: The idea of augmented reality also drives the development of many other related technologies, including wearables, haptic technologies and many others that have been featured in this column. Findings: Developers invest in the future based on the idea that widespread use of augmented reality is just around the corner. Yet in many ways, it still appears to be a technology eternally on the cusp of mainstream adoption. Originality/value: In 2014, this column looked at augmented reality as an important emerging technology. Nearly three years later, some libraries continue to use it in groundbreaking ways, and it has grown by leaps and bounds.